8(2x-2)=2(3x+1)-28

Simple and best practice solution for 8(2x-2)=2(3x+1)-28 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(2x-2)=2(3x+1)-28 equation:


Simplifying
8(2x + -2) = 2(3x + 1) + -28

Reorder the terms:
8(-2 + 2x) = 2(3x + 1) + -28
(-2 * 8 + 2x * 8) = 2(3x + 1) + -28
(-16 + 16x) = 2(3x + 1) + -28

Reorder the terms:
-16 + 16x = 2(1 + 3x) + -28
-16 + 16x = (1 * 2 + 3x * 2) + -28
-16 + 16x = (2 + 6x) + -28

Reorder the terms:
-16 + 16x = 2 + -28 + 6x

Combine like terms: 2 + -28 = -26
-16 + 16x = -26 + 6x

Solving
-16 + 16x = -26 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-16 + 16x + -6x = -26 + 6x + -6x

Combine like terms: 16x + -6x = 10x
-16 + 10x = -26 + 6x + -6x

Combine like terms: 6x + -6x = 0
-16 + 10x = -26 + 0
-16 + 10x = -26

Add '16' to each side of the equation.
-16 + 16 + 10x = -26 + 16

Combine like terms: -16 + 16 = 0
0 + 10x = -26 + 16
10x = -26 + 16

Combine like terms: -26 + 16 = -10
10x = -10

Divide each side by '10'.
x = -1

Simplifying
x = -1

See similar equations:

| 4m^2-25/4 | | -10.5+m+11.57= | | 4(3y-1)=-18 | | 1x-9=15 | | 25v^2+40vp+16p^2= | | 6(2X-9)-5=6(X-4)+1 | | 1/2+9/12 | | 3(w+13)=89 | | X^2+22x-203=0 | | 2[d-(2d+18)+13]=2(d+5) | | 16=2e | | 4(8x+32)=64 | | -5v-3+2=22 | | 9(2x-4)=3(6x+8) | | 8x+2=3x+13 | | -29=-7y-9y | | 36m^2-49/25 | | 14=24 | | 5+9t-2=9t+17-7t | | 9d+5-2d=20 | | x/6=42 | | 24=-2(6a-7) | | 3(x-0.8)=4x-4 | | 3x-21-7x+20= | | 1+2/x+5/x^2=0 | | 1/2+9/x=5/4 | | 10-2p=4q | | 12-3p=q | | 3x+16x=95 | | 7-2(1-3s)=35 | | -21+[-14+(-13)]= | | 15-p=q |

Equations solver categories